A study of nursing car in patients with fracture and dislocation of cervical spinal cord in educational hospitals of Tehran University of Medical Sciences - Farahnaz Danandeh; Farideh Yaghmaei; Farrokh Sohail; Parviz Kamali (Iran University of Medical Sciences, 1993)
This descriptive study was aimed to identify how provided nursing care related to physical problems caused by traction and cast in patients with fracture and dislocation in cervical spinal cord in educational hospitals of Tehran University of Medical Sciences. Samples, including 46 patients were recruited from neurosurgery and orthopedic wards, and also from Neurosurgical Intensive Care Units during 8 months period. Results showed that nursing care provided by nurses were in a proper level. There was no significant relationship between variables such as age, gender, level of education, kind of neurological lesions and provided nursing care. A significant relationship between cervical lesion and provided nursing care was found